Ex vivo evaluation of the effect of photodynamic therapy on skin scars and striae distensae. Issue 5 (1st June 2015) - Mendoza‐Garcia, Jenifer; Sebastian, Anil; Alonso‐Rasgado, Teresa; Bayat, Ardeshir
Summary Background Skin scars and striae distensae (SD) are common dermal disorders with ill‐defined treatment options. There is emerging clinical evidence for use of photodynamic therapy (PDT) in treating skin fibrosis. Therefore, the aim here was to investigate the effect of PDT on skin scars and SD in an ex vivo model of human skin scarring. Methods Photodynamic therapy, with 5ALA or MALA in addition to illumination with 40 J/cm2 of red light, was applied to striae alba, fine line, hypertrophic and keloid scars ex vivo (n = 18). General morphology was assessed by H&E, Herovici's and Weigert's differential staining. Apoptosis, proliferation, metalloproteinase 3 and tropoelastin expression were quantified immunohistochemically, and differential gene expression of proliferating cell nuclear antigen (PCNA), collagen (COL) type I and type III, matrix metalloproteinase 3 (MMP3) and tropoelastin (ELN) was assessed by real‐time quantitative reverse transcription polymerase chain reaction. Results Apoptosis increased, which correlated with decreased proliferation and PCNA gene expression. Post‐PDT, matrix components were found to be re‐organised in both hypertrophic and keloid scars. COLI and COLIII gene expression levels decreased, whilst MMP3 and ELN increased significantly post‐PDT compared to normal skin and untreated controls (P < 0.05). However, no significant difference between 5ALA and MALA‐PDT treatments was observed. Conclusion Using our unique ex vivo model, we show for the first time morphological and cellular effect of application of PDT, which correlates with the degree and severity of dermal fibrosis. In view of this, PDT may be ideal in targeting treatment of abnormal skin scarring.